2005
DOI: 10.1590/s0102-695x2005000300015
|View full text |Cite
|
Sign up to set email alerts
|

Influência da temperatura de secagem e da concentração de Aerosil®200 nas características dos extratos secos por aspersão da Schinus terebinthifolius Raddi (Anacardiaceae)

Abstract: RESUMO:A Schinus terebinthifolius Raddi é muito usada na medicina popular e atualmente como fi tomedicamento pelas propriedades antimicrobiana, cicatrizante e antiinfl amatória. O objetivo deste trabalho foi avaliar a infl uência da temperatura de entrada e a concentração

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 4 publications
2
13
0
7
Order By: Relevance
“…This behavior is in agreement with previous work on plant extract spray-drying with colloidal silicon dioxide [15]. On the other hand, as shown in Table 3, the use of higher feed flow rates (C) gave more moist powders due to higher water loads for evaporation.…”
Section: Moisture Contentsupporting
confidence: 92%
See 2 more Smart Citations
“…This behavior is in agreement with previous work on plant extract spray-drying with colloidal silicon dioxide [15]. On the other hand, as shown in Table 3, the use of higher feed flow rates (C) gave more moist powders due to higher water loads for evaporation.…”
Section: Moisture Contentsupporting
confidence: 92%
“…In those cases, higher inlet thermal levels led to lower powder moisture contents. Nevertheless, for Schinus terebinthifolius Raddi -plant extract -spray-drying with high concentrations of Aerosil 200 as drying adjuvant, Vasconcelos et al [15] found that the inlet temperature did not affect powder residual moisture content.…”
Section: Moisture Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…; Vasconcelos et al . ). The use of biopolymers has been the focus of a growing number of studies on their potential.…”
Section: Discussionmentioning
confidence: 97%
“…New technologies to modernize the preparation of traditional herbs as part of pharmaceutical products are being evaluated with the ultimate goal of maximizing the opportunities and overcoming the challenges inherent to herbal medicines (Vasconcelos et al, 2005;Yadav & Dixit, 2008).…”
Section: Dissolution Testsmentioning
confidence: 99%